Flow velocity field of the Saigon River section during operation of flood control structures - Irina M. Markova; Phan Khanh Khanh (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. Vietnam’s largest economic centre, Ho Chi Minh City, is facing riverbank erosion, one of the main causes of which is runoff. In this study, the flow velocity field of the Saigon River section is analyzed in different time periods.Materials and methods. Data on discharge, water level, river network topography and river channel were collected to set up simulation models in the programmes MIKE 11 and MIKE 21. These programmes are the main tools used in the study.Results. The current velocity in the middle of the river is 3–4 times higher than on the two banks. However, during the period between high and low tide, the current on both sides of the river has higher speed than the main stream, especially in the upper part of the winding banks, such as the part of the river from Ben Nghe sluice to Tan Thuan sluice and the section of the river from An Loi Dong police station to Thu Thiem 2 bridge. The velocity values in the studied river section in most cases exceed the allowable erosion-free velocity values of particles of channel material, river banks, and suspended sediment particles. The operation of the flood control sluices will slightly reduce the flow velocity values and also cause whirlpools in front of the sluices.Conclusions. The MIKE 11 and MIKE 21 software detailed the flow distribution of the Saigon River. The flow velocity on the Saigon River has a complex distribution and varies from period to period depending on the flood discharge from the Dau Tieng Reservoir and the tidal currents of the East Sea. The process of erosion on both sides of the river will occur regularly and continuously, so urgent measures are needed to protect the riverbank.